Pentingnya Tata Kelola Informasi Pada Organisasi Publik - admin, admin (STISOSPOL WASKITA DHARMA, 2019)
Information governance is currently being echoed in the field of administrative organization. along with the development of information technology and internet networks that no longer provide time and space limits for each individual in communicating and accessing information. In a public organization, especially in government in the current digitization era, access to public information really needs to be developed and managed access. Information governance encourages the openness of the state apparatus in providing information management and data management services as well as more systematic transparency and accountability of the bureaucratic process. The application of an information governance must be in accordance with the rights and decision specifications and the accountability framework. the aim is to ensure compliance with the assessment, creation, storage, use, archiving and deletion of information in a public organization. Keywords: governance, information, public organizations.